Development of the Social-Media Assisted Listening 'Think-Pair-Share' Learning Model During a Pandemic - Syofianis Ismail (International Journal on Integrated Education, 2021)
This research was initiated on the preliminary studies in the English Language Education program in studying Interpretative listening courses to see the condition and need of the teaching listening. The fact showed that 1) the teacher-centered model was still used in the classroom; 2) learning listening comprehension was not optimal yet and teaching model applied was incapable to develop; 3) There are many problems found by lecturers and teachers in how to become an effective listener. This study aims to develop a valid, effective, and practical Social Media Assisted Learning Listening Think Pair Share Learning (SmartPLS) model, using YouTube and Whatsapp. Developing this model is important because Social media; especially video YouTube can improve students' Listening Comprehension significantly. The study used Research and Development (R & D) approach. The development procedure used was an ADDIE model which consists of analysis, design, development, implementation, and evaluation. The researcher involved several experts to validate the design, content, and presentation of this model. The subject of the limited trial involved 10 students and the field sample was 38 students of English Language Education of the Islamic University of Riau who were taking the basic listening course. The data were collected through a questionnaire and analyzed quantitatively by using Excel. The result of this study found that the SmartPLS model is considered effective, valid, and practice and that it can be used to improve four Listening skills: 1) determine vocabulary meaning from context; 2) identifying the main idea with supporting details; 3) Listening for a specific purpose; and 4) recognizing specific grammatical structures within a setting for students.